2015
DOI: 10.1007/s00405-015-3870-8
|View full text |Cite
|
Sign up to set email alerts
|

Infiltration with lidocaine and adrenaline instead of normal saline does not improve the septoplasty procedure

Abstract: The aim of this study was to determine whether infiltration of local anesthetics with adrenaline improved septoplasty procedure when compared to normal saline. Eight-two patients undergoing septoplasty were randomized into two groups. In group 1, septal mucoperichondrium was infiltrated with lidocaine with adrenaline, and normal saline was used in group 2. Presence of intra-operative septal mucosal injuries, the amount of bleeding, arterial blood pressure, operation time as well as the quality of the surgical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
1
5
1
Order By: Relevance
“…In Group I there was very little bleed so surgical plane was readily accessed but Group II Patients experienced frequent surgical field flooding which made surgical access difficult and time taking. This finding was totally in contrast to some of the previous studies 4,6 which showed that that there is no significant difference between adrenaline and normal saline. But in these studies by Mahilravi Thevasagayam et al and Volkan Gungor et al the concentration of adrenaline used was different and more so it was used in combination with lignocaine.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In Group I there was very little bleed so surgical plane was readily accessed but Group II Patients experienced frequent surgical field flooding which made surgical access difficult and time taking. This finding was totally in contrast to some of the previous studies 4,6 which showed that that there is no significant difference between adrenaline and normal saline. But in these studies by Mahilravi Thevasagayam et al and Volkan Gungor et al the concentration of adrenaline used was different and more so it was used in combination with lignocaine.…”
Section: Discussioncontrasting
confidence: 99%
“…Rationale behind using adrenaline and normal saline in this study is that they are easily available, cost effective and already being used in most hospitals all over the world [4][5][6] but in various combinations. Variables used to assess the efficacy of submucoperichondrial infiltration solutions are both subjective as well as objective which can gauge the effectiveness of these solutions accurately.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Saline tumescence could be consider as the reference solution injected, but in our patients we used lidocaine with vasoconstrictor as described above. Gungor et al [10] denied the benefits of anesthetic tumescent rhinoplasty. However, in his study he concludes that there was no benefits in terms of bleeding decrease or mucosal injury prevention, in our opinion it concedes us the possibility to do a complete rhinoplasty only with local anesthetics, which is impossible otherwise if normal saline is only injected.…”
Section: Discussionmentioning
confidence: 99%